Healthy Eating in Population Models of Nutrition: Asian Diet Style Summary - O. B. Shvabskaia; N. S. Karamnova; O. V. Izmailova; O. M. Drapkina (Рациональная фармакотерапия в кардиологии)
The population of Japan and Okinawa is known for the longest life expectancy, which many researchers rightly associate with the nature of nutrition existing in these territories. The Japanese diet and Okinawan diet, along with other traditional diets, are real examples of historically established sustainable patterns of healthy eating. Asian eating styles have marked differences from European eating patterns, not only in differences in food sources, but also in eating habits. The article presents the historical, climatic and cultural features of these diets; the issues of food composition, energy and nutritional value of these models of nutrition are considered in detail with an analysis of the differences existing between them; highlights the benefits of products grown mainly in Japan, which are ration-forming for the population of this country; as well as the results of scientific studies on the protective effect of the Japanese and Okinawan diets on human health and disease prevention.